Dampak Good University Governance terhadap Kinerja Perguruan Tinggi - Taufik Hidayat (Journal on Education, 2023)
The purpose of this study was to determine the effect of good university governance on university performance. This research method uses quantitative with an associative approach. The samples used in this study were 199 respondents who were on the campuses of the Syarif Hidayatullah State Islamic University Jakarta and the Ahmad Dahlan Institute of Technology and Business Jakarta. The sampling method used is purposive sampling. The data collection method uses primary data by distributing questionnaires to stakeholders. The results of the study show that Good University Govenance has an effect on the performance of Higher Education.